Assessment Of Direct Observe Treatment Short Course (Dots) Implementation and Treatment Card Update by Dot Providers Under Revised National Tuberculosis Control Programme in Raipur District of Chhattisgarh State - Bhawnani, Dhiraj; Verma, Nirmal; Soni, Gopal P; Tiwari, Anjana (National Journal of Community Medicine, 2014)
Background: DOTS is the backbone of RNTCP and its proper implementation is the key of success of programme, in which DOT providers play a crucial role. Chhattisgarh is unexplored area related to research in national health programme like RNTCP which need due priority, hence district level health system research relevant to TB is reason to select current research study. So the present study was conducted to assess the DOTS implementation and treatment card update by DOT providers underRevised National Tuberculosis Control Programmein Raipur district of Chhattisgarh state. Methodology: A cross sectional observational community based study was conducted usingsimple random sampling in all 33 Designated Microscopic Centres (DMC’s) of Raipur district from November 2011 to October 2012. During the study, 136 DOT providers were included and predesigned and pretested proforma was used as a study tool. The obtained data were analyzed using appropriate statistical test. Results: Majority of DOT providers were between 30-40 year and 83.8% were female. Majority (63.4%) were mitanin (ASHA). The modular training was received by only 9.6% of DOT providers and rest were spot trained. Proper implementation of DOTS was seen in 13.2% DOT centres & Treatment cards update was found in 9.5% only. Conclusion: Proper DOTS implementation and treatment card update was very low, so there is urgently need to ensure the same.